Implementasi Sistem Pengelolaan Pengaduan Online dalam Pelayanan Publik: Studi Kasus SP4N Lapor - M. Harry Mulya Zein; M. Adam Rifaldi; Sisca Septiani (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effectiveness of the SP4N LAPOR application in managing public service complaints by the Communication and Information Agency of Muara Enim Regency, South Sumatra Province. Using a qualitative approach with a descriptive method, this study evaluates the effectiveness of the application through three main dimensions: achievement of objectives, integration, and adaptation. The study results indicate that the implementation of SP4N LAPOR has not been optimal due to several obstacles, particularly the lack of coordination and communication between relevant agencies. The study also identified various factors hindering the application's effectiveness, such as slow response times to public complaints and insufficient awareness about the application's use. Despite these challenges, the local government continues to improve the system, including establishing communication channels through WhatsApp groups between agencies and providing various platforms for submitting complaints. This research contributes to understanding how digital complaint management systems can be implemented more effectively in the local government context.